Zypern: Insel ohne Geschäftsmodell? - David Bencek; Bianka Dettmer; Klaus Schrader (Wirtschaftsdienst, 2013)
Im Zuge der Krise hat sich Zypern vom südeuropäischen Erfolgsmodell zum Schuldenstaat entwickelt. Die Autoren analysieren, wie es dazu kommen konnte und welche Möglichkeiten Zypern bleiben, um den wirtschaftlichen Niedergang zu stoppen und auf einen Wachstumspfad zurückzukehren. – – Cyprus appeared to be a South European success story until the beginning of the economic and financial crisis in 2008. But in early 2013, the country was at the edge of bankruptcy, its leading banks were illiquid, its economy was shrinking and unemployment was rising. Against this background, this article analyses which factors contributed to the Cypriot crash and how the country can achieve an economic revival. Due to the lack of industrial competence, it is suggested to revive the Cypriot service industry in the course of a reunification of Cyprus. A reunification could rebuild confidence lost during the crisis, create synergy effects in tourism and facilitate natural gas production.
Keywords: F14; F15; F34; 330